Income Tax Credits for Consumer Services: A Tool for Tackling VAT Evasion? - Thiess Büttner; Boryana Madzharova; Orlando Zaddach (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper analyzes the effects of an income tax credit for hard-to-tax consumer services on evasion of the value-added-tax (VAT). Based on the individual tax files of the universe of VAT payers in Germany, our analysis shows that harnessing incentives for consumers through tax credits fosters firms' compliance with VAT by bringing in an element of third-party reporting at the last VAT stage. Our results point at strong stimulating effects of the introduction of the tax credit on reported sales as well as on the ratio of reported sales to inputs. We find limited price effects. While two thirds of the revenue losses in the income tax are recovered by an increase in VAT revenues, up to half of the revenue gain is associated with a response at the VAT evasion margin. The policy thus fosters considerable formalization effects.
Keywords: H26; H25; H24; 330; tax compliance; value-added tax; income tax credit; third-party reporting